Colonization of extended-spectrum β-lactamase-producing Enterobacteriaceae does not affect subsequent infection and liver transplant outcomes: a retrospective observational cohort study - Shang, Chen; Yang, Run; Yang, Ya; Zhang, Haomin; Zhang, Jianjun; Xia, Qiang; Gao, Yuan; Deng, Yuxiao (Frontiers in Public Health, 2023)
Objective To investigate the colonization rate of Extended-Spectrum β-Lactamase-Producing Enterobacteriaceae (ESBL-E), subsequent infections by ESBL-E and ESBL-producing gramnegative bacilli (ESBL-GNB), and the effect of ESBL-E colonization on clinical outcomes in liver transplantation (LT) recipients. Methods This is a retrospective cohort study that included patients who underwent LT at Shanghai Renji Hospital between July 2016 and December 2017. Rectal swabs from LT patients at the postoperative ICU enrollment were screened anonymously for ESBL-E carriage. Demographics data, laboratory indexes, operative complications, and clinical course information were also obtained. The extent of ESBL-E colonization, the subsequent infection rates of ESBL-E and ESBL-GNB, and the clinical outcomes were compared between ESBL-E colonized and non-colonized patients.In total, 496 liver transplant recipients (387 males) were included in this study. ESBL-E colonization was detected in 240 patients (48.4%). There was no significant difference between the rates of ESBL-E infection (5.8% vs. 3.1%, p = 0.143), Ischemia-reperfusion ≥ 3 (27.9% vs. 24.6%, p = 0.403), acute kidney injury (39.6% vs. 38.7%, p = 0.835), acute rejection (2.1% vs. 1.6%, p = 0.664), graft versus host reaction (1.3% vs. 1.2%, p = 0.937), duration of hospitalization (22 days vs. 23 days, p = 0.568), 90-day mortality (7.1% vs. 4.7%, p = 0.262) and one-year mortality (12.9% vs. 9.3%, p = 0.265) in patients with and without ESBL-E colonization. Though the ESBL-GNB infection rate was higher in ESBL-E colonized patients (12.1% vs. 6.6%, p = 0.037), multivariate analysis showed that ESBL-E colonization did not increase the risk of ESBL-GNB infection (Model 1: aOR 1.755, 95% CI: 0.911-3.380, p = 0.093; Model 2: aOR 1.556, 95% CI: 0.761-3.181, p = 0.226). The ESBL-producing bacteria spectrum of colonization was significantly different from that of infections occurring after LT, with only three colonization events leading to infection by the same pathogen identified.ESBL-E colonization in liver transplant patients is not associated with ESBL-E infection, nor is it a risk factor for post-transplant ESBL-GNB infection. Additionally, ESBL-E colonization does not lead to worse prognoses when compared with non-colonized patients.